2018
DOI: 10.1088/1367-2630/aad140
|View full text |Cite
|
Sign up to set email alerts
|

Doubly effects of information sharing on interdependent network reciprocity

Abstract: Understanding large-scale cooperation among unrelated individuals is one of the greatest challenges of the 21st century. Since human cooperation evolves on social networks, the theoretical framework of multilayer networks is perfectly suited for studying this fascinating aspect of our biology. To that effect, we here study the cooperation in evolutionary games on interdependent networks, such that players in one network layer play the snowdrift game (SDG), and the prisoner's dilemma game (PDG) in the other lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…While the bulk of research concerning evolutionary games on networks has been devoted to single and isolated networks, such as small-world [20][21][22][23][24][25][26], scale-free [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], coevolving [42][43][44][45][46][47][48][49][50], hierarchical [51,52] and community [53] networks, the focus has in recent years been shifting towards multilayer and interdependent networks [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. This research has revealed interdependent network reciproci...…”
Section: Introductionmentioning
confidence: 99%
“…While the bulk of research concerning evolutionary games on networks has been devoted to single and isolated networks, such as small-world [20][21][22][23][24][25][26], scale-free [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], coevolving [42][43][44][45][46][47][48][49][50], hierarchical [51,52] and community [53] networks, the focus has in recent years been shifting towards multilayer and interdependent networks [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. This research has revealed interdependent network reciproci...…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between psychologists and economists have been marked more by conflict than by collaboration and the absence of a common research language impedes communication between this the disciplines (Manski, 2017). Some of the studies describe the relationship between psychologists and economists (Croson and Miller, 2004;Attanasi and Rosemarie Nagel, 2008;Schotter and Trevin, 2014;De Bruin and Fischhoff, 2017;Xia et al, 2018). In this section, we review and interpret Prisoner's Dilemma with the help of the concept of hyper-rationality.…”
Section: Behavior Of Individuals In Human Societiesmentioning
confidence: 99%
“…The studies of complex networks have provided many novel ideas and insights for understanding the structure and dynamics of complex systems, such as social ties that link different people and transportation networks that connect different cities [1][2][3][4][5]. In recent years, research efforts have shifted from studying each complex system as a single and isolated network to synthesizing multiple correlated systems as interdependent, multiplex or multilayer networks [6][7][8][9][10][11]. This evolving trend indeed echoes modern technical advancements, such as the Internet of Things, Smart Grid, Ubiquitous Computing, Mobile Web, Big Data and Artificial Intelligence, which contribute a novel perspective that different complex systems often have strong correlations and they can interact with each other through nontrivial means.…”
Section: Introductionmentioning
confidence: 99%